Structure and function of the insulin receptor: its role during lactation and foetal development - Deleo, Domenica (Curtin University, 1994)
Prior to the commencement of this study in 1990, a number of reports had appeared in the literature describing the importance of insulin action during lactation in mammals (see Chapter 1). These studies investigated the changes in circulating insulin and glucagon concentrations during lactation, the relative numbers of insulin receptors in insulin-sensitive tissues, and glucose utilisation by these tissues. However, at that time, no information was available on the structure of the mammary insulin receptor. The rationale for undertaking this study was to characterise the structure of the rat mammary insulin receptor as a means of furthering our understanding of the role insulin plays during lactation.An initial requirement of this study was the development of a method for the convenient and inexpensive preparation of A14-tyrosyl[125I]iodoinsulin. A14-tyrosyl[125I]iodoinsulin displays binding characteristics which are virtually indistinguishable from the native hormone, which is a necessary requirement for tracers which are to be used in binding studies. In Chapter 2, I describe a method for the purification of A14-tyrosyl[125I]iodoinsulin from a mixture of iodinated insulin molecules which are produced following oxidation by chloramine-T in the presence of Na125iodine. In this method I employed disposable cartridges packed with a C18 support matrix to which the iodinated insulin molecules are readily adsorbed when in an aqueous solution.A 14-tyrosyl[125I]iodoinsulin absorbed most strongly to the C18 matrix and unwanted products were removed through a sequence of washes prior to the elution of the A14-tyrosyl[125I]iodoinsulin derivative using a buffer containing 50% (v/v) acetonitrile. This prodct was unambiguously shown to be A14-tyrosyl[125I]iodoinsulin by N-terminal amino acid sequencing. The quality of this radiolabel compared favourably with commercially available A14-tyrosyl[125I]iodoinsulin preparations both in terms of specific activity and stability upon storage at -20C. Furthermore, a modified method based on this protocol has been used in our and other laboratories for the isolation of other iodinated peptides with highly satisfactory results.I have established that the size of the a-subunit of the rat mammary insulin receptor is significantly diminished compared with the liver insulin receptor (125 kDa versus 130 kDa). This difference in size was present throughout all stages of lactation and was not due to proteolysis of a larger form. Furthermore, I demonstrated that both the mammary and liver insulin receptor a-subunits migrated equally on PAGE following treatment with neuraminidase, indicating that the apparent size difference may be accounted for by a variation in the extent of receptor sialation. Treatment of the mammary insulin receptor a-subunit with glycopeptidase F demonstrated that the size of the aglycoreceptor (100 kDa) was similar to that described for insulin receptors from other insulin-sensitive tissues.I characterised the distribution of mRNA encoding the two, naturally-occurring insulin receptor isoforms in mammary tissue throughout all stages of pregnancy and lactation. These insulin receptor isoforms differ due to the absence (IR-A) or presence (IR-B) of a 12 amino acid peptide, encoded by exon 11 of the insulin receptor gene, and located near the C-terminus of the insulin receptor a-subunit. Mammary tissue predominantly expressed IR-A mRNA in contrast to liver tissue, which almost exclusively expressed IRB mRNA. Furthermore, the ratio of IR-A to IR-B mRNA in mammary tissue changed significantly during the first week post-partum whilst the distribution of IR-A and IR-B mRNA in the liver remained constant throughout pregnancy and lactation. This difference in insulin receptor isoform expression between mammary and liver tissue also contributed to the estimated size difference between the insulin receptor a-subunits from these two tissues. In addition, I characterised the expression of IR-A and IR-B mRNA in several different tissues obtained from rats on day 14 of gestation through to 7 days post partum. I established that the splicing mechanism is functional at least as early as day 14 of gestation, suggesting a possible role for the preferential expression of a particular insulin receptor isoform during organogenesis. I observed that IR-A mRNA was the predominant isoform in all foetal tissue studied, and the proportion of this isoform declined as the animal matured. These changes were significant in cardiac muscle, kidney and most dramatic in the liver where the expression of IR-A mRNA changed from 53% in the 21 day old foetus (the day before parturition) to 13% in the 1 day old neonate. These results suggest that the splicing mechanism which generates the receptor isoforms is subject to acute hormonal and/or metabolic control.The current literature suggests that the carbohydrate moieties of the insulin receptor affects its affinity for insulin. Furthermore, the IR-A and IR-B isoforms have been shown to display a 2-fold difference in their insulin binding affinity when expressed in heterologous cell lines such at CHO cells or Rat-1 fibroblasts. Since both glycosylational and isoform distribution differences were evident between mammary and liver tissues, the insulin binding affinities of these receptors were compared. Estimates of the binding affinity parameters were performed at both 4 C and 37 C. At both temperatures the equilibrium binding constants for mammary and liver tissues were not significantly different suggesting that structural variations of the mammary insulin receptor had no effect on the insulin binding affinity under the conditions described in this study. Comparison of the 4 C and 37 C binding data showed that the mammary insulin receptor exhibited complex, temperature-dependent binding characteristics, similar to those previously described for the liver insulin receptor, and entirely consistent with the presence of a temperature-dependent regulatory protein that affects insulin binding.